Development of Robotic Coordinated Control System for Bowl Food Packaging. (September 2019) - Yequan, Bao; Changsheng, Ai; Dunyang, Geng; Gangchang, Ren; Hong, Ju
Abstract: The processing of the bowled food is relatively mechanical, repetitive and cumbersome, resulting in high work intensity, low efficiency, and high defect rate, and meets the working cycle:13.5s, positioning accuracy: 2mm.A PLC-based automatic feeding control system for food packaging line was designed. Including the conveyor line for bowl feeding, the numerical controlled manipulator and package process following control system for reclaiming and discharging functions, the system control scheme was proposed and 3D modeling construction was carried out. The design of hardware and software for feeding, reclaiming and discharging in the system is elaborated in detail. Finally, through the actual on-site commissioning and production operation, it is proved that the equipment has fully met the design requirements and greatly improved the production efficiency.